Using cognitive mapping to foster deeper learning with complex problems in a computer-based environment. - Wang, Minhong; Wu, Bian; Kirschner, Paul A.; Michael Spector, J. (Computers in Human Behavior, 2018)
Concept mapping has been widely used to foster meaningful learning and support the communication of complex ideas. With a focus on conceptual understanding, traditional concept mapping is found to be inadequate in supporting problem solving particularly in eliciting and representing the complex process of applying knowledge to practice. In this study, a computer-based cognitive-mapping approach was used to extend traditional concept mapping by allowing learners to represent the problem-solving process and the underlying knowledge in a visual format. By representing ideas both verbally and pictorially, the cognitive mapping approach has a high potential to foster effective thinking and reflection in problem-solving contexts. This study examined the effects of the computer-based cognitive-mapping approach by comparing it to a note-taking approach that represents ideas in verbal text only. Forty-nine senior year medical students participated in the study. The experimental group used the cognitive-mapping approach, while the control group used a note-taking approach, to articulate complex thinking and actions when working with simulated clinical diagnostic problems in a computer-based learning environment. The results show the promising effects of the cognitive-mapping approach on improving students' problem-solving performance, subject-matter knowledge, and intrinsic motivation to learn with complex problems.